Penguatan Peran Kader Kesehatan Melalui Pendampingan Dan Pelatihan Tentang Kesiapan Menyusui Sejak Hamil Dan Gerakan Menyusui Eksklusif - Pratiwi Puji Lestari; Siti Maria Ulfa (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Exclusive breastfeeding has been shown to have many health benefits for infants, including protection against infection, chronic disease, and neonatal death. It is important for mothers who experience breastfeeding problems to seek support from a trained health care provider or lactation consultant. The purpose of this community service is to provide skills to health cadres to provide assistance in breastfeeding readiness for pregnant women. The community service method used is training for cadres through refreshing knowledge about lactation preparation and exclusive breastfeeding. The interactive lecture method and practice are carried out by roleplay. The cadres who participated were 8 cadres from the Sungai Jingah Health Center area. The results of the cadre assessment are one of the indicators of the achievement of the objectives of the training activities carried out. With the increasing knowledge of the cadres, cadres are expected to be able to provide assistance to pregnant women to prepare for breastfeeding so that they can help increase the success of breastfeeding. Overall, assistance on breastfeeding readiness since pregnancy plays an important role in ensuring that mothers and babies get maximum benefits from the breastfeeding process.